The Importance of Trust and Deliberation In Leadership From A Hadith Perspective - Chaliddin Chaliddin; Munawar Khalil (Siyasah Wa Qanuniyah, 2025)
Leadership (imamah) in Islam plays a vital role in maintaining the ummah's social order, justice, and moral integrity. This study aims to explore the hadiths concerning the mandate and responsibility of Islamic leaders, particularly focusing on the principles of shura (consultation) and amanah (trust), and to contextualise them within modern leadership theories. Using a qualitative library research method, this paper conducts a thematic and comparative analysis of prophetic traditions related to leadership. It examines their relevance in light of contemporary theories such as deliberative democracy and ethical leadership. The findings show that while the Qur'an does not explicitly mention "leadership," it emphasises values such as consultation, trust, and justice, principles further reinforced in the Hadith. These values serve as the moral foundation of leadership in Islam and align with modern concepts of participatory governance, accountability, and servant leadership. This study concludes that Islamic leadership, rooted in the principles of shura, amanah, and ‘is, offers a value-based, participatory, and transformative leadership model. These principles align with modern theories such as deliberative democracy, ethical leadership, and good governance, but also provide a relevant alternative to address contemporary leadership challenges such as ethical crises, lack of public trust, and weak participation.